Справочное пособие электромонтера в строительстве - Гайдукевич Владислав Иванович (Стройиздат, 1986)
Экземпляры: ф.1 (20191211☮) / Инвентарный номер: 14420 / Цена: 01.10 / Сис.шифр: 31.29 / Авт.знак: Г14 / ББК: 31.29-5я22